Fifty most cited Turkish Orthopedics and Traumatology articles in international literature: A bibliometric analysis (Annals of Medical Research, 2021)
Aim: The aim of this study is to identify the 50 most cited Turkish papers in international Orthopedic literature and analyze them to define the subconscious scientific behaviors of Turkish Orthopedic surgeons and the contributive characteristics of Turkish Orthopedic surgeons for the science at the last four decade. Material and Methods: WoS Core Collection was searched for the Turkish Orthopedic articles between 1980 and 2019 in all fields with pre-defined terms. Data including the number citations, age of the article, subcategories, number of authors, journals names, impact factors and publishers, institution names, numbers and categories, Level of Evidence (LoE) and article language were collected. A correlation analysis (Pearson for parametric and Spearman for nonparametric values) was performedbetween the impact factors and citation numbers (C), and also citation rates (C/R). A chi-square test was performed between citation numbers and levels of evidence. A value of p 0.05 was considered to be statistically significant.Results: All of the 50 articles were original articles that were written in English. The citation counts were between 164 and 44. The article ages were between 27(C:60, C/R: 2.22/yr) and 2(C: 50, C/R: 25/yr). Tweenty-three different journals were found in the analysis. The mean level of evidence (LoE) was found 3. 84% of the papers were studied in a University hospital.Conclusion: This bibliometric study showed no statistically significant correlation between the data analyzed. On the other hand, this study also revealed once again that there was no correlation between citation numbers and journal impact factors as expected. Additionally, this study also showed that Turkish Orthopedic scientists are getting citations independent of journal impact factors.
Keywords: Bibliometric; citation; study; traumatology; Turkish; orthopedic